Let $f_q(x)$ be the generating function of the sequence $(q;q)_n$: $$f_q(x):=\sum_{n=0}^{\infty} (q;q)_n x^n,$$ where $(q;q)_n: = (1-q)(1-q^2) \cdots (1-q^n)$ with convention $(q;q)_0$:=1.

Let $g_q(x):=1/f_q(x)$.

Question: Are there closed form expressions for $$\lim_{x \rightarrow 1} g'_q(x) \quad \mbox{and} \quad \lim_{x \rightarrow 1} g''_q(x) \quad ?$$ By a rather tricky argument, I get $\lim_{x \rightarrow 1} g'_q(x) = -(q;q)_{\infty}$. But I don't get anything simple for $\lim_{x \rightarrow 1} g''_q(x)$.


We have $$f_q(x)=(q;q)_{\infty}\sum_{n\ge 0}\left(\frac{1}{(q^{n+1};q)_{\infty}}-1\right)x^n+(q;q)_{\infty}\frac{1}{1-x}.$$ Note that \begin{equation} \frac{1}{(q^{n+1};q)_{\infty}}-1=\exp\left(\sum_{\ell\ge 1}\frac{q^{(n+1)\ell}}{\ell(1-q^{\ell})}\right)-1\ll \frac{|q|^n}{(|q|;|q|)_{\infty}} \end{equation} for sufficiently large $n$. Thus $$h_q(x):=\sum_{n\ge 0}\left(\frac{1}{(q^{n+1};q)_{\infty}}-1\right)x^n$$ is analytic for $|x|<|q|^{-1}$.
Hence for $|q|<1$, $$(q;q)_{\infty}g_q(1-x)=\frac{x}{xh_q(1-x)+1}$$ is analytic for $|1-x|<1/|q|$. Further for $|1-x|<1/|q|$, \begin{align} h_q(1-x)&=\sum_{n\ge 0}\left(\frac{1}{(q^{n+1};q)_{\infty}}-1\right)\sum_{r=0}^n(-1)^{n-r}\binom{n}{r}x^r\\ &=\sum_{r\ge 0}(-x)^r\sum_{n\ge r}(-1)^n\binom{n}{r}\left(\frac{1}{(q^{n+1};q)_{\infty}}-1\right):=\sum_{r\ge 0}\alpha_r(q)x^r. \end{align}

In particular, we have \begin{align} (q;q)_{\infty}g_q(1-x)&=\frac{x}{1+\sum_{r\ge 1}\alpha_{r-1}x^r}\\ &=x-\alpha_1(q)x^2+(\alpha_1(q)^2-\alpha_2(q))x^3+\dots \end{align} The following is easy!

  • $\begingroup$ Amazing! Is this an instance of some general method, or did you invent all of it for this particular question?? $\endgroup$ – მამუკა ჯიბლაძე Jul 22 '18 at 18:18

From $q$-binomial theorem we have \begin{align} f_q(x)&=(q;q)_{\infty}\sum_{n\ge 0}\frac{x^n}{(q^{n+1};q)_{\infty}}\\ &=(q;q)_{\infty}\sum_{n\ge 0}x^n\sum_{k\ge 0}\frac{q^{(n+1)k}}{(q;q)_{k}}=(q;q)_{\infty}\sum_{k\ge 0}\frac{q^{k}}{(q;q)_{k}}\frac{1}{1-xq^k} \end{align} for all $|q|<1$ and $|x|<1$. Therefore for $|1+x|<1$ and $|x|<|q^{-k}-1|, k\ge 1$, \begin{align} \frac{f_q(1+x)}{(q;q)_{\infty}}&=-\frac{1}{x}+\sum_{k\ge 1}\frac{q^{k}}{(q;q)_{k}}\frac{1}{1-q^k-xq^k}\\ &=-\frac{1}{x}+\sum_{k\ge 1}\frac{q^{k}}{(q;q)_{k}}\frac{1}{1-q^k}\sum_{r\ge 0}\left(\frac{q^k}{1-q^k}\right)^rx^r\\ &=-\frac{1}{x}+\sum_{r\ge 0}x^r\sum_{k\ge 1}\frac{1}{(q;q)_{k}} \left(\frac{q^k}{1-q^k}\right)^{r+1}. \end{align} Now, we see that $$\frac{f_q(1+x)}{(q;q)_{\infty}}+\frac{1}{x}$$ is an analytic function for $$x\in\{z\in\mathbb{C}:|z|<|q^{-k}-1|, k=1,2,\dots\}:=\Omega_q.$$ It is clear that $\Omega_q\neq\emptyset$ is an open set for $|q|<1$. We further have \begin{align} \frac{xf_q(1+x)}{(q;q)_{\infty}}&=-1+\sum_{r\ge 1}x^{r}\sum_{k\ge 1}\frac{1}{(q;q)_{k}} \left(\frac{q^k}{1-q^k}\right)^{r}:=-1+\sum_{r\ge 1}A_r(q)x^r. \end{align} Hence $$(q;q)_{\infty}g_q(1+x)=\frac{-x}{1-\sum_{r\ge 1}A_r(q)x^r}=-x-A_1(q)x^2-(A_2(q)+A_1(q)^2)x^3-\dots$$ is an analytic function at $x=0$. Thus, $$g_q'(1)=-\frac{1}{(q;q)_{\infty}}\quad\mbox{and}\quad g_q''(1)=-\frac{2}{(q;q)_{\infty}}\sum_{k\ge 1}\frac{1}{(q;q)_{k}}\frac{q^k}{1-q^k}.$$

  • $\begingroup$ Care to elaborate how you're applying the $q$-binomial theorem? I don't see any $q$-binomial coefficients around... $\endgroup$ – darij grinberg Aug 19 '18 at 11:22
  • $\begingroup$ Ah, I see. Your second equality sign follows from the identity $\dfrac{1}{\left(x;q\right)_\infty} = \sum\limits_{k\geq 0} \dfrac{x^k}{\left(q;q\right)_k}$, which appears on en.wikipedia.org/wiki/Q-Pochhammer_symbol#Identities . I still don't see what this identity has to do with the $q$-binomial identity, but at least I see how to prove it: For any $m \geq 0$ and $n \geq 0$, the coefficient of $x^m q^n$ on the left hand side counts the partitions of $n$ into at most $m$ parts, while the coefficient of $x^m q^n$ on the right ... $\endgroup$ – darij grinberg Aug 19 '18 at 11:27
  • $\begingroup$ ... side counts the partitions of $n$ such that each parts is $\leq m$. But there is a bijection between the former and the latter partitions, given by conjugation (= transposition). $\endgroup$ – darij grinberg Aug 19 '18 at 11:28
  • $\begingroup$ From what I understand, $f_q\left(1-x\right)$ is not well-defined. But $\dfrac{f_q\left(1-x\right)}{\left(q;q\right)_\infty}$ is well-defined (as a formal power series in $q$ and $x$), because your equality $\dfrac{f_q\left(x\right)}{\left(q;q\right)_\infty} = \sum\limits_{k\geq 0} \dfrac{q^k}{\left(q;q\right)_k} \cdot \dfrac{1}{1-xq^k}$ shows that $\dfrac{f_q\left(x\right)}{\left(q;q\right)_\infty} \in \mathbb{Q}\left[x\right]\left[\left[q\right]\right]$ and we can substitute $1-x$ for the polynomial indeterminate $x$. But how do you get a $\dfrac{1}{x}$ in the result? $\endgroup$ – darij grinberg Aug 19 '18 at 11:38
  • $\begingroup$ @ darij grinberg $1/x$ is from $\sum_{k\ge 0}\frac{q^k}{(q;q)_k}\frac{1}{1-xq^k}$ with $k=0$ and substitute $1−x$ to $x$. $\endgroup$ – Zhou Aug 19 '18 at 12:42

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.